Governance, maternal well-being and early childhood caries in 3-5-year-old children - Morenike Oluwatoyin Folayan; Maha El Tantawi; Ana Vukovic; Robert J. Schroth; Micheal Alade; Simin Z. Mohebbi; Ola B. Al-Batayneh; Arheiam Arheiam; Rosa Amalia; Balgis Gaffar; Nneka Kate Onyejaka; Hamideh Daryanavard; et al. (BMC, 2020)
Abstract Background This study assessed the direct, indirect and total effect of distal - political - risk indicators (affecting populations), and proximal risk indicators (affecting women) on the global prevalence of early childhood caries (ECC) in 3-5 year old children. Methods Data on global ECC prevalence were obtained from a prior study. Data for distal risk indicators (voice and accountability; political stability/absence of terrorism; control of corruption) were obtained from the World Bank Governance indicators, 2016. Data for proximal risk indicators (women's opportunity for leadership; percentage of female legislators, top officials and managers; basic employability status of women; ability of women to afford time off work to care for newborns; gross national income (GNI) per capita for females) were derived from the Human Development Index, 2016. Associations between variables were assessed with path analysis. Results Voice and accountability (β = − 0.60) and GNI per capita for females (β = − 0.33) were directly associated with a lower ECC prevalence. Political stability/absence of terrorism (β =0.40) and higher percentage of female legislators, senior officials and managers (β = 0.18) were directly associated with a higher ECC prevalence. Control of corruption (β = − 0.23) was indirectly associated with a lower ECC prevalence. Voice and accountability (β = 0.12) was indirectly associated with a higher ECC prevalence. Overall, voice and accountability (β = − 0.49), political stability/absence of terrorism (β = 0.34) and higher female GNI (β = − 0.33) had the greatest effects on ECC prevalence. Conclusion Distal risk indicators may have a stronger impact on ECC prevalence than do proximal risk indicators.. Approaches to control ECC may need to include political reforms.